Pemanfaatan E-Office sebagai Praktik Paperless Office - Hani Damayanti Aprilia; Akgis Cahyaningtias (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2022)
Companies need a system that can support company activities by utilizing information technology. This system is expected to assist and facilitate the management of the company's activities to run effectively and efficiently. This system is then called the electronic office or electronic office (e-office). This study aims to determine the use of e-office as a paperless office practice in life insurance companies. This research is case study research with a qualitative approach. The selection of informants was done intentionally (purposivesampling). Collecting data using participatory observation, in-depth interviews, and documentation. Meanwhile, for data analysis using an interactive model developed by Miles & Huberman to test the validity of the data using triangulation techniques. The results show that the e-office used by life insurance companies is very complete. Apart from being intended for marketers to complete work, the use of e-office can also be used by marketers to establish communication with customers. Utilization of e-office for marketers is not only to achieve job targets, but can also be used to assess performance. With the eoffice,companies can not only save time but also cut paper costs and also the cost of sending letters/documents. Therefore, by utilizing the e-office application, the company's target to implement a paperless office as a solution to environmental issues can be achieved.